Do age complementarities affect labour productivity? Evidence from German firm level data - Cornelius Peters (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In Germany as in many other European countries there will be a shift in the age structure of the workforce in the next decades. The number of older workers will increase whereas the number of young and middle aged workers will decline. This paper provides evidence how the demographic ageing affects labor productivity. It focuses on age complementarities between workers. Using a cross sectional linked employer-employee data set from 2012 translog cost functions are estimated. To maintain consistency with microeconomic theory, several parameter constraints are imposed. To control for the skill level of the workers a nested production structure is applied. In addition, this allows to analyse the complementarities between different age groups by skill level. Based on the estimated parameters pairwise elasticities of complementarity and factor price elasticities are calculated. The results indicate that workers belonging to different age groups are complementary factors. The complementarities especially arise between young and medium aged workers and are higher within groups of high skilled labor. Simulating the expected shift in the age structure due to the demographic ageing indicates that the productivity of younger and middle aged workers will increase whereas the productivity of older workers will decline due to the complementary relationship between the different age groups.
Keywords: C31; D24; J11; 330